Expanding Knowledge About Music and Well-Being in Carceral Settings: A Methodological Review. - Im, Vitalis; Pinto, Rogério M. (International Journal of Offender Therapy & Comparative Criminology, 2025)
This methodological review includes literature (1987–2022) concerning the role and influence of musical practices—including music therapy and participatory music interventions—on well-being in carceral settings such as jails, prisons, and immigration detention centers. We provide a thorough description of key methodological procedures used in 55 studies: (1) Key Elements of Research Questions; (2) Types of Musical Practices; (3) Musical Genres; (4) Methodologies and Designs; (5) Locations; (6) Theoretical Frameworks; and (7) Samples. Our review indicates that there is difficulty in conducting research in prisons due to limitations imposed on researchers, a paucity of randomized-control trials, and limited generalizability of results due to the heterogeneity of methodological approaches. We suggest that the literature base would benefit from increased attention to issues related to sampling procedures, research questions related to race and gender identity, as well as the delineation between the types of musical practices utilized by music interventions.